2016
DOI: 10.2147/ndt.s109633
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal spontaneous regional brain activity in primary insomnia: a resting-state functional magnetic resonance imaging study

Abstract: ObjectiveInvestigating functional specialization is crucial for a complete understanding of the neural mechanisms of primary insomnia (PI). Resting-state functional magnetic resonance imaging (fMRI) is a useful tool to explore the functional specialization of PI. However, only a few studies have focused on the functional specialization of PI using resting-state fMRI and results of these studies were far from consistent. Thus, the current study aimed to investigate functional specialization of PI using resting-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 35 publications
3
49
0
Order By: Relevance
“…In a recent study, Chen et al discovered that female insomniacs had increased activation of the anterior insula with salience networks, and they further revealed the relationship between blood-oxygen-level dependent (BOLD) in insula and the EEG gamma frequency power (Chen et al, 2014). Li et al also reported a stronger connectivity between the bilateral superior parietal lobe and the right insular lobe in insomnia (Li et al, 2014). More recently, Wang et al found an increased regional homogeneity (ReHo) value in the left insula in insomnia patients (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a recent study, Chen et al discovered that female insomniacs had increased activation of the anterior insula with salience networks, and they further revealed the relationship between blood-oxygen-level dependent (BOLD) in insula and the EEG gamma frequency power (Chen et al, 2014). Li et al also reported a stronger connectivity between the bilateral superior parietal lobe and the right insular lobe in insomnia (Li et al, 2014). More recently, Wang et al found an increased regional homogeneity (ReHo) value in the left insula in insomnia patients (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Using task-based fMRI, Martin et al reported that poor quality sleepers showed smaller activations in the right IFG, right MFG, and bilateral insula compared with good quality sleepers during an immediate and impulsive monetary decision task (Martin et al, 2015). By using the superior parietal lobe (SPL) as a seed, Li et al illustrated that insomnia patients exhibited increased connectivity between the SPL and the right IFGtri, right insula lobe, right ventral anterior cingulate cortex (ACC), left ventral posterior cingulate cortex, and right splenium of the corpus callosum, which represent brain regions critical for spatial and verbal working memory (Li et al, 2014). Moreover, Altena et al discovered that insomnia patients showed a hypoactivation in the IFG during performance in a category and letter fluency task, which recovered after sleep therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research results of fMRI and structural neuroimaging studies are not consistent with our results. They do not have a relationship with the PFC25 or exhibit different areas associated with insomnia symptoms 24,26,62…”
Section: Discussionmentioning
confidence: 99%
“…Second, the different methodologies may affect the discrepancies in results. In this study, we utilized VFT, whereas previous studies observed correlations under the no-task state 2426,62. Finally, the diversity of clinical manifestations of insomnia patients and duration of insomnia symptoms may contribute to the discrepancy 24,35,36…”
Section: Discussionmentioning
confidence: 99%
“…Findings primarily showed greater brain entropy and reduced rsFC in PI within important brain structures (e.g., hippocampus) and networks (e.g., DMN), and these rsFC differences correlated with scores on the Pittsburgh Sleep Quality Index (PSQI, Buysse et al, 1989b). Other such rsFC measures used to compare PI and controls include amplitude of low frequency fluctuations (ALFF) and regional homogeneity (ReHo), and investigators using these approaches have suggested that differences may reflect hyperarousal in PI (Dai et al, 2016; Dai et al, 2014; Li et al, 2016a). Importantly, these measures have also been shown to correlate with PSQI scores.…”
Section: Introductionmentioning
confidence: 99%